DIGITALISASI DI PERPUSTAKAAN PERGURUAN TINGGI MELALUI DATABASE GOOGLE SCHOLAR: NARRATIVE LITERATURE REVIEW - Reginawati Silalahi; Rully Khairul Anwar; Siti Chaerani Djen Amar; Evi Nursanti Rukaman (BIBLIOTIKA : Jurnal Kajian Perpustakaan dan Informasi, 2023)
Library collection is defined as one of the important components in library development.  This research uses a narrative literature review method from references related to the topic of book digitization in college libraries. Collection digitization is needed to preserve the contents of the library's print collection which can be damaged. The existence of a digital library that has advantages in access speed because it is oriented in digital data and computer network media, it also requires digitization of print collections.